Composite nanofiltration membrane with tannic acid coordinated collagen fibers for enhanced molecule separation - Xie, Yinshan (2024)
Biomass-based membranes have attracted increasing attentions due to their cheap and sustainable advantages. In this work, a novel thin-film composite (TFC) nanofiltration (NF) membrane was fabricated through a facial interfacial polymerization (IP) process by initiate the crosslinking reaction between collagen fibers (CFs) and tannic acid (TA). The increased TA concentrations endowed the TFC membrane with a higher crosslinking degree, a thicker active layer and a rougher top surface. At optimized condition with 0.60 mg TA decoration, the TFC-3 membrane exhibited a high water permeability of 23.49 L m−2 h−1 bar−1 with high rejections above 98.0% for congo red, reactive blue 19, coomassie blue G-250, and methyl blue. Furthermore, the membrane preserved remarkable salt retentions (93.3% for Na2SO4, 83.4% for MgSO4, 36.2% for MgCl2, and 26.4% for NaCl) and satisfying operation stability. This facial fabrication method offered a new insight to employ biomass for molecular precise separation.